Da’wah in Household Product Advertisements: A Reception Study of Islamic Values in Nawaitu Sahaja TV Advertisements - Rahmania Santoso; Desi Dwi Prianti (Humaniora, 2022)
In Indonesian contemporary society, spirituality and religion can be used to create Islamic brand identities. In order to promote the intended identity, marketers use advertisements to reach their target audience. Sahaja, an Indonesian brand of home care products, uses Islamic identity as part of their strategic communication. Using their Nawaitu Sahaja advertisements, they promote the da’wah (promotion of Islam) message. This research aimed to examine how a Muslim audience receives the Islamic da’wah used by Nawaitu Sahaja. To understand how audiences, receive the Islamic values portrayed in the Nawaitu Sahaja advertisements, seven women who are part of Nasyiatul Aisyiyah – an Islamic women’s organis ation – were interviewed in 2021. In order to promote their products, Nawaitu Sahaja advocates the importance of making a clean and hygienic home as part of one’s Islamic values. Baiti Jannati ("my home is my heaven") is the main message in these advertisements. Using Stuart Hall’s reception analysis, this research found different reading positions. Such reading positions were influenced by the audience's views on the message of Islamic values. Participants’ interpretations of the da’wah message in the Nawaitu Sahaja advertisements was found to be dominant. Using Islamic messages in advertisements is thus one way of engaging with consumers and encouraging them to purchase the products therein.